Protection of Homeowners in Russia from Unlawful Encroachment on Their Rights and Legitimate Interests - EVGRAFOVA, Irina V.; MARCHENKO, Alexander V.; TRAVIN, Alexander V. (Journal of Advanced Research in Law and Economics; Vol 10 No 1 (2019): JARLE Volume X Issue 1(39) Spring 2019, 2019)
The relevance of the study is due to the fact that with the initiation of the new Housing Code of the Russian Federation the situation with the provision of housing rights has not radically changed for the better. In this context, the article aims to analyze the features of civil-legal regulation of housing relations, ensuring the constitutional rights of citizens to housing, ways of committing offenses in the sphere of residential properties and their preventive actions, the problem of improving the legislation. Leading approach to the study of this problem is the descriptive method that has afforded revealing peculiarities of regulation of civil and housing legislation under consideration within Russian Federation. In the article the suggestions for improving the legislation of Russian Federation are presented. The materials of the paper imply the practical significance for the university teachers of the legal specializations.